2018
DOI: 10.1002/asia.201801447
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Thermometry by a Y/Eu Binary Layered Rare‐Earth Hydroxide (LRH) via In Situ Intercalation with Neutral Terbium(III) Complexes

Abstract: Temperature‐sensitive luminescent materials have aroused great interest for practical applications in optical sensors. Layered rare‐earth hydroxides (LRHs) possess rich interlayer chemistry and adjustable composition; thus, they are the promising candidates for designing functional materials, usually through an ion exchange process. Herein, the intercalation of neutral TbIII complex rather than ion exchange was successfully performed in situ into the gallery of Y/Eu binary LRHs by using a hydrothermal process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Structurally, LRHs are similar to LDHs but the component sheets are more complicated because the rare-earth metal ions form two distinct coordination polyhedra, with 8 and 9 vertices. 47 The ability of LRHs to exhibit magnetic and fluorescent properties arising from the rare-earth metal ions they contain has fostered increasing interest in their applications in medical imaging, 48,49 as optical sensors, [50][51][52][53] and as tuneable phosphors. 54,55 In addition, like LDHs, their layered structure also allows LRHs to be used in conventional applications such as sequestration and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, LRHs are similar to LDHs but the component sheets are more complicated because the rare-earth metal ions form two distinct coordination polyhedra, with 8 and 9 vertices. 47 The ability of LRHs to exhibit magnetic and fluorescent properties arising from the rare-earth metal ions they contain has fostered increasing interest in their applications in medical imaging, 48,49 as optical sensors, [50][51][52][53] and as tuneable phosphors. 54,55 In addition, like LDHs, their layered structure also allows LRHs to be used in conventional applications such as sequestration and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The PLE spectrum, recorded by monitoring the red emission at 613 nm ( 5 D 0 → 7 F 2 transition of Eu 3+ ), exhibits a broad transition band ranging from 200 to 300 nm, with a maximum at ~209 nm and two broad shoulders at ~234 nm, ~270 nm (Figure A). These are the transitions by charge transfer (CT), that is, the electronic transition from the 2 p orbital of O 2− to the 4 f orbital of Eu 3+ activators . Because yttrium ions occupy nine independent crystallographic positions, Eu 3+ ions, that replace Y 3+ ions, are randomly distributed in these sites, resulting in various CT band centers arising from the different Eu–O bond lengths .…”
Section: Resultsmentioning
confidence: 99%
“…These are the transitions by charge transfer (CT), that is, the electronic transition from the 2p orbital of O 2− to the 4f orbital of Eu 3+ activators. [25][26][27] Because yttrium ions occupy nine independent crystallographic positions, Eu 3+ ions, that replace Y 3+ ions, are randomly distributed in these sites, resulting in various CT band centers arising from the different Eu-O bond lengths. 3 The excitation peaks at ~320 nm, ~350-420 nm (with the maximum at ~394 nm), and ~465 nm are the intra-4f electronic transitions of Eu 3+ , which are 7 F 0,1 → 5 H 3 , 5 H 6 , 7 F 0,1 → 5 L 6 , and 7 F 0,1 → 5 D 2 , respectively.…”
Section: Photo-and Electro-luminescence Behavior Of Y 3 Bo 6 :Eu 3+mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the solid-solution phosphor always exhibits orange-red emission at 590 nm. While under exposure to UV light, YBO 3 : Tb 3+ displays the typical green emission at~546 nm ( 5 D 4 → 7 F 5 transition of Tb 3+ ), and color-tunable photoluminescence can be found in solid solution phosphor of Y/Tb/Eu ternary system through an efficient energy transfer from Tb 3+ to Eu 3+ ions [18][19][20]. Recently, it was reported that doping Bi 3+ in rare-earth borates could effectively manipulate the synthetic/thermal stable temperature [21].…”
Section: Introductionmentioning
confidence: 99%